can someone please check these and let me know if these are correct or if they are wrong can I have a few pointers or advise.
1. Determine the remainder when x³-6x²+x-5 is divided by:
a. X+2
f(x) = x³ - 6x² + x - 5
(x+2)= f(-2) = (-2)³ - 6(-2)² + (-2) - 5
-8 - 24 - 2 - 5 = -39
b. X-3
f(x)= x³ - 6x² + x-5
(x-3)=f(3)³ - 6(3)² + (3) - 5
27-72+3-5= -43
1. Determine the remainder when x³-6x²+x-5 is divided by:
a. X+2
f(x) = x³ - 6x² + x - 5
(x+2)= f(-2) = (-2)³ - 6(-2)² + (-2) - 5
-8 - 24 - 2 - 5 = -39
b. X-3
f(x)= x³ - 6x² + x-5
(x-3)=f(3)³ - 6(3)² + (3) - 5
27-72+3-5= -43
Last edited: